The Effect of Glycerol and Chitosan Variation Composition on the Quality of Biodegradable Plastics from Sugar Palm Starch (Arenga pinnata) - Oninda Bella Shavira; Ahmad Fuadi (CHEMICA: Jurnal Teknik Kimia, 2021)
Bioplastics are plastics that are easily degraded in nature, which can minimize their potential as pollutants. It is mainly made from agro-polymers such as cellulose and starch. Starch from sugar palm (Arenga pinnata) has the gelatinization principle and requires bioplastic raw materials by adding glycerol and chitosan. This research aims to determine the effect of addition glycerol and chitosan composition variation on the bioplastic mechanical properties. The research method used a completely randomized design method factorial (RAL-factorial) with one treatment factor carried out in 2 stages. The first step was mixing 4 grams of sugar palm starch and chitosan with variations (5 grams, 6 grams, and 7 grams). The second step was mixing starch and chitosan with glycerol with variations (2 mL and 3 mL). Based on data provided by statistics and mechanical nature tests, it could be concluded that the more volume of glycerol and chitosan added, the value of tensile strength will increase; on the contrary, the elongation value at the break, air resistance, biodegradation increases. The value of air resistance is 109.37%, with the composition of glycerol 3 mL and chitosan 5 grams. The tensile strength value is 11 Mpa with the composition of glycerol 3 mL and chitosan 7 grams. The elongation value is 6.67%, with the composition of glycerol 3 mL and chitosan 5 grams. The biodegradation increase is 79% with the composition of glycerol 2 mL and chitosan 5 grams.